High‐frequency ultrasound quantification of acute radiation dermatitis: pilot study of patients undergoing radiotherapy for breast cancer. Issue 4 (17th May 2017) - Garnier, M.; Champeaux, E.; Laurent, E.; Boehm, A.; Briard, O.; Wachter, T.; Vaillant, L.; Patat, F.; Bens, G.; Machet, L.
Abstract : Background: Acute radiation dermatitis (ARD) is a frequent complication after breast cancer radiotherapy and is usually assessed by semi‐quantitative clinical scores, which may be subject to inter‐observer variability. High‐frequency ultrasound imaging of the skin can reliably quantify thickness and edema in diseased skin. We aimed to compare the relative increase in dermal thickness of the irradiated zone in breast‐cancer patients undergoing radiotherapy, with clinical severity. Methods: A consecutive series of patients undergoing treatment for breast cancer by lumpectomy and radiotherapy in a 6‐month period also underwent clinical and ultrasound evaluation of ARD. Results: We included 34 female patients 17 had grade 1 (group 1), 17 had grade 2 or grade 3 ARD (group 2). The mean relative increase in dermal thickness in irradiated skin (RIDTIS) was greater for group 2 than 1: 0.53 vs 0.29 mm ( P =.023). On univariate analysis, ARD was associated with skin phototype, breast volume and RIDTIS, and on multivariable analysis, breast volume and age remained predictive of the disease. Conclusion: Patients with more severe dermatitis showed significantly increased dermal thickness. Dermal thickness is a quantitative variable that could help quantify the efficacy of drugs and improve the treatment of this disease in patients undergoing radiotherapy.